Cigarette smoke impairs granulosa cell proliferation and oocyte growth after exposure cessation in young Swiss mice: an experimental study - Paixão Larissa LO; Gaspar-Reis Rejane P; Gonzalez Gabrielle PL; Santos Aline S; Santana Aluana C; Santos Rachel MM; Spritzer Mara Poli; Nascimento-Saba Celly Cristina A (BMC, 2012)
Abstract Background Cigarette smoke is associated with decreased female fertility, causing damage to ovarian function and disturbing follicle development. However, the effects of cigarette toxicants on ovarian function depend on duration and intensity of exposure. The aim of this study was to assess the effects of brief, intense exposure to tobacco smoke on granulosa cell number, oocyte growth, and follicle size during puberty in female Swiss mice. Methods Ten female Swiss mice aged 35 days were exposed to tobacco smoke from 3R4F reference research cigarettes. They were exposed to an automatic smoking machine 8 h/day, 7 days/week for 15 days. Ten age-matched controls were kept in a different room and exposed to ambient air. At the end of 15 days, five mice in each group were euthanized and the ovaries were analyzed for follicular morphometry and granulosa cell count. The remaining animals were kept for an additional 30 days for further analysis as an ex-smoker group and control group. Comparison between the two groups was evaluated by the Student's t-test or a two-way ANOVA followed by Bonferroni post-test was applied for multiple comparisons. Results We found that cigarette smoke impaired antral follicular growth even after exposure cessation (p < 0.001). Both smoking and ex-smoking groups exhibited similar follicle diameter. However, at the same follicular stage, the number of granulosa cells was smaller in the ex-smoking group compared to smoking animals (p < 0.001). This was associated with increased oocyte diameter in ex-smoking animals compared to smoking animals (p < 0.01). Conclusions The negative effects of cigarette smoking seem to last even after exposure has been interrupted. Moreover, brief exposure during puberty may induce silent oocyte disruption, which could in turn lead to decreased fecundity rates.